The determinants of microcredit loans repayment problem at Bank Simpanan Nasional (BSN) Kota Bharu / Suriani Mohamad - Mohamad, Suriani (2013)
The microcredit loans are able to improve the economic and social status of the poor since it provides a working opportunity. Apart of the challenges in offering the microcredit loan, the micro finance institutions also having challenge with loan repayment. The aim of this paper is to investigate the determinants of microcredit loans repayment problem at Bank Simpanan Nasional (BSN) Kota Bharu. The primary data used in this study is gathered through a survey on 100 borrowers from BSN Micro Finance in Kota Bharu. By using Multiple Regression Analysis and Pearson Correlations are employed to identify whether the three determinants have relationship with loans repayment problem. The findings show that all the three determinants; borrower characteristics, business characteristics and microcredit loan characteristics have positive relationship with loans repayment problem. Meanwhile, the business characteristics have the greatest impact towards the loans repayment problem among the three independent variables